Strengthening The Role of Local Community in Developing Countries Through Community-Based Tourism from Education Perspective: Bibliometric Analysis - Purwanti Dyah Pramanik; Myrza Rahmanita (Indonesian Journal of Multidiciplinary Research, 2023)
Community-based Tourism (CBT) provides sustainability principles, local community participation, and benefits for local communities. The research aims to present the strengthening of the role of the local community in developing countries through CBT and find research gaps related to factors to strengthen the role of the local community in developing countries through CBT. The methodology was a narrative review. Papers were collected from ScienceDirect and Google Scholar links in 1999-2023, using the keyword "community-based-tourism," and applied inclusion/ exclusion criteria. Eighty-two papers were processed using a VOS viewer. The results reveal that strengthening the role of the local community through CBT still faces internal and external challenges. However, there are some opportunities to strengthen the role of the local community in the themes of power and empowerment. Since most of the CBT research was in the context of uptown, future research should be conducted in downtown.